Endocrine resistance in hormone-responsive breast cancer: mechanisms and therapeutic strategies. Issue 8 (August 2016) - Murphy, Conleth G; Dickler, Maura N
Abstract : The majority of breast cancers may be considered hormone responsive due to expression of hormone receptors (HR+). Although endocrine therapy is always considered for advanced HR+ breast cancer, the emergence of resistance is inevitable over time and is present from the start in a proportion of patients. In this review, we explore the mechanisms underlying de novo and acquired resistance to endocrine therapy. We comprehensively review newly approved and emerging therapies that have been developed to counteract specific mechanisms of resistance. We discuss the challenges pertinent to this therapeutic arena including the potential relief of negative regulatory feedback inhibition with compensatory pathway activation and the evolution of molecular changes in HR+ breast cancers during treatment. We discuss strategies to address these challenges in order to develop rational therapy approaches for patients with advanced HR+ breast cancer.